PENERAPAN MEDIA MONTASE UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS V SD NEGERI 07/III SUNGAI ABU KABUPATEN KERINCI - Asiah, Siti; Musyaffa, A A; Idris, Ilyas; Meinal, Istari Rezkia (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study discusses the application of montage media to improve the speaking skills of fifth grade students at SD Negeri 07/III Sungai Abu, Kerinci Regency. The cycle process which includes four stages, namely planning, implementation, observation and reflection becomes part of the implementation of this research. Based on observation, interview and documentation techniques, the data obtained is then processed through data reduction, data display, and drawing conclusions. The results of the study found that the application of montage media to improve students' speaking skills was carried out in the following steps: (1) the teacher used a storytelling strategy (2) the teacher prepared tools and drawing materials from various references according to the sub-theme of learning material in the form of newspapers, magazines, Or pictures from the internet. (3) the teacher divides students classically from groups consisting of 4-5 students per group, in pairs then individually. (4) the teacher gives rewards such as a shining star symbol. Whereas the results of the learning process on speaking skills are shown from the results in each cycle that has been carried out, the achievement is with an average pre-action of 44.42%, the first cycle has increased to an average of 54.80% while the second cycle has increased significantly to 80.57%.